(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Rahayu EMD, Yusri S. 2021. Habitat preferences of wild orchids in Bantimurung Bulusaraung National Park to model their suitable habitat in South Sulawesi, Indonesia. Biodiversitas 23: 43-54. Wild orchids are mainly threatened by habitat degradation and over-exploitation. Orchid conservation requires information regarding its distribution and suitable habitat, and factors affecting it. This study aimed to investigate the distribution and habitat preferences of orchids in Bantimurung Bulusaraung National Park, Sulawesi, Indonesia, and to predict the habitat suitability map of orchids in South Sulawesi, Indonesia. The survey was conducted in Bantimurung Bulusaraung National Park to collect data on orchid occurrences along with microhabitat characteristics (altitude, light, temperature, substrate thickness, and vertical distribution). ERGo Datasets Landforms and Physiography, SRTM elevation, NDVI derived from LANDSAT 8 OLI were used in Google Earth Engine to obtain macrohabitat data. Microhabitat preference of environmental data was averaged for each variable and further explored with Canonical Correlation Analysis. Suitable habitat was modeled with Maxent using occurrences and environmental data. The survey found 26 epiphytic orchid species and 22 phorophyte species. Orchids were found at an altitude from 514 m to 933 m above sea level. Altitude is the most discriminant factor in determining orchids’ distribution in the study area. The Maxent analysis showed that the suitable habitat of orchids comprises of 3,554.952 km2 area which is mainly located in lowland rainforest with high topographic diversity, preferably warm slope, and ridges. Since lower slope and lowland areas are not protected, community-based conservation such as social forestry can become one of the alternative solutions for in situ conservation of orchids. For ex-situ conservation, integrated orchid conservation in botanic gardens should be prioritized.